(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical characteristics and evaluate the use of totally implantable venous access ports in patients with head and neck cancer receiving chemotherapy. Materials and methods: A prospective descriptive study was conducted on 35 patients with head and neck cancer who were indicated for chemotherapy and underwent totally implantable venous access port insertion at the Department of Medical Oncology I, Nghe An Oncology Hospital, from 03/ 2025 to 08/2025. Outcome measures included complications, port functionality, pain severity, adherence to the nursing care protocol, and patient satisfaction. Result: The mean age of the participants was 61.03 ± 7.9 years, and all patients were male. Hypopharyngeal - laryngeal cancer was the most common primary tumor site (57.1%), and the majority of patients were diagnosed at stage III–IV (94.3%). Port implantation was performed before the initiation of chemotherapy in 77.1% of patients, and 94.3% of the catheters were inserted via the right internal jugular vein. Pain during port access was generally mild, with 71.4% of patients reporting a Visual Analog Scale (VAS) score of 2. Adherence to the standardized nursing care protocol was achieved in 91.4% of cases. The complication rate was low, including one case of local infection (2.9%) and one case of catheter occlusion (2.9%). Adherence to the nursing care protocol was significantly associated with a lower complication rate (p = 0.005). Overall, 74.3% of patients reported being satisfied or very satisfied with the implanted port. Conclusion: Totally implantable venous access ports demonstrated a low complication rate, good port functionality, mild pain, and high patient satisfaction in patients with head and neck cancer receiving chemotherapy. Adherence to standardized nursing care protocols was associated with a significantly lower rate of port-related complications.